JUSTIFICATION OF THE FEASIBILITY OF THE DEVELOPMENT OF FINANCIAL AND LEGAL REGULATION OF THE CRYPTOCURRENCY MARKET IN THE LIGHT OF GLOBALIZATION - Zavada, Taras (Global Prosperity, 2022)
The article examines the feasibility of developing the financial and legal regulation of the cryptocurrency market in light of globalization. The author considered the historical and legal context of the formation of the cryptocurrency market against the background of globalization. The author characterized the content of blockchain technology, its features as a subject of financial and legal regulation of cryptocurrency and the content of financial and legal relations arising in connection with the functioning of cryptocurrency markets. The author came to a conclusion that although blockchain technology is able to solve a number of problems related to the functioning of financial markets, it still creates a number of threats to the national interests of the state in the financial sphere. The author substantiates the feasibility of the development of financial and legal regulation of the cryptocurrency market in light of globalization in connection with the spread of threats of fraud, tax evasion, the use of cryptocurrencies to pay for illegal goods and services, and the financing of terrorism.